Social Protection, Food Security and Nutrition An Update of Concepts, Evidence and Select Practices in South Asia and Beyond - Gentilini, Ugo (The World Bank, 2022)
A leading economist recently stated that "food security may be the defining global challenge of the Century." And in underscoring the importance of social protection, the head of an international organization declared that "[w]e must recognize, share, scale up and build on these successful measures." In a way, this volume aims to help bridge these two worlds - that of food security and nutrition, on the one hand, and that of social protection, on the other - by reflecting on how the mechanisms of the latter might be employed to address the needs of the former
Keywords: Cash Transfers; COVID-19; Early Warning Systems; Food and Nutrition Policy; Food Security; Health, Nutrition and Population; Nutrition; Social Protections and Assistance; Social Protections and Labor